Timing of glucocorticoid administration determines severity of lipid metabolism and behavioral effects in rats. (2nd January 2017) - Wu, Tao; Jiang, Jianguo; Yang, Luna; Li, Haifeng; Zhang, Wanjing; Chen, Yangyang; Zhao, Binggong; Kong, Boda; Lu, Ping; Zhao, Zhenzhen; Zhu, Jiawei; Fu, Zhengwei
ABSTRACT: Glucocorticoids (GCs) are a group of steroid hormones secreted by the adrenal glands in circadian cycles, and the dysregulation of GC signaling has been suggested to cause metabolic syndrome. Even though prolonged GC exposure is associated with serious side effects such as metabolic syndrome and central nervous system disorders, the use of GCs in anti-inflammatory and immunosuppressive therapies has been continuously rising. Meanwhile, the exact mechanisms by which GCs can influence the lipid metabolism as well as behavior and how they are affected by time remain unknown. In this study, the effects of two different long-term GC dosing regimens on lipid metabolism and behavior were investigated. Male Wistar rats received daily administrations of the GC dexamethasone sodium phosphate (DEX, 0.5 mg/kg body weight) at either ZT0 (Dex0) or ZT12 (Dex12). After 6 weeks of treatment, DEX-treated rats, especially those treated at ZT0, had higher hepatic lipid accumulation and serum triglyceride levels and less locomotor activity than did control rats. In addition, serum levels of corticosterone, 5-hydroxy tryptamine and norepinephrine were decreased in the Dex0 group but not in the Dex12 group compared to the control group. Furthermore, quantitative real-time polymerase chain reaction analysis indicated that the chronic administration of GCs at ZT0 upregulated genes related to glycolysis and lipid synthesis and downregulated genes related to fatty acid β-oxidation in the liver more remarkably than administration at ZT12. Both DEX-treated groups displayed severely altered expression patterns of the core clock genes Bmal1 and Per2 in the liver and in fat. In addition, the expression of g lutamate aspartate transporter, glial fibrillary acidic protein and glutamate transporter-1, astrocyte-related genes important for maintaining nervous system functions, was drastically decreased in the hippocampus of DEX-treated rats, especially when DEX was given at ZT0. In conclusion, our findings confirm that the severity of side effects, indicated by altered lipid metabolism and behavioral activity, depends on the timing of GC administration and is associated with the degree of glucocorticoid receptor dysfunction after dosing at disparate time points.